Bridge Failures and Mitigation Using Monitoring Technologies - Baş, Selçuk; Catbas, F. Necati; Baş, Selçuk (Springer Science and Business Media Deutschland GmbH, 2021)
The current study aims to understand the reasons for bridge failures. It considers the recent damages and collapses of in-service real bridge structures and discusses mitigation methods based on monitoring technologies. Transportation systems serve a crucial function in the strategies for mitigating bridge damages and failures. After investigating recent damages and failures in real bridges, structural bridge failures are classified in this study according to their safety and operational function. For each function, global and local level failures are also defined with two groups: major/long-span and highway bridges. In the light of this classification, structural monitoring methods are identified according to global and local failures. Along with standard Structural Health Monitoring (SHM) systems with comprehensive sensor networks, at vision-based SHM system and developments in this area are shown to provide some opportunities for mitigation of bridge failures resulting from service loads rather than natural hazard-induced failures. © 2021 Elsevier B.V., All rights reserved.
Keywords: [No Keywords]